3D small strain large deflection beam shape sensing including poisson effect. (15th April 2020) - Schaefer, Pierre-Loup; Chagnon, Grégory; Moreau-Gaudry, Alexandre
Highlights: Poisson effect on beam cross section is included with specific strain model. Bending, torsion, tensile and shearing deformations are recovered from strain. Reconstruction accuracy is improved compared to axial strain based beam shape sensing. Poisson effect influences estimation of bending and tension compression. Abstract: This article presents a new method to monitor beam shapes from strain measures. The beam is instrumented with strain sensors placed on its surface with an angle of orientation. The method developed is a 3D large deflection beam shape reconstruction based on a beam model incorporating Poisson effect and is thus able to take into account bending, torsion, shearing and tensile-compression deformations. Exemple of application on circular beams is conducted with beam shape reconstructed from FEM simulations strain measures. Results show that, compared to beam shape sensing methods using axial strain, the beam shape method proposed provides a significant increase in the reconstruction accuracy when the beam is subject to deformations containing torsion.